Diffraction properties of a strongly bent diamond crystal used as a dispersive spectrometer for XFEL pulses. (11th June 2019) - Samoylova, Liubov; Boesenberg, Ulrike; Chumakov, Aleksandr; Kaganer, Vladimir; Petrov, Ilia; Roth, Thomas; Rüffer, Rudolf; Sinn, Harald; Terentyev, Sergey; Madsen, Anders
Abstract : Diffraction properties of strongly bent defect‐free diamond crystals have been measured and compared with the modelling based on the Takagi–Taupin equations. Abstract : Self‐amplified spontaneous emission (SASE) enables X‐ray free‐electron lasers (XFELs) to generate hard X‐ray pulses of sub‐100 fs duration. However, due to the stochastic nature of SASE, the energy spectrum fluctuates from pulse to pulse. Many experiments that employ XFEL radiation require the resolution of the spectrum of each pulse. The work presented here investigates the capacity of a thin strongly bent diamond crystal to resolve the energy spectra of hard X‐ray SASE pulses by studying its diffraction properties. Rocking curves of the symmetric C*(440) reflection have been measured for different bending radii. The experimental data match the theoretical modelling based on the Takagi–Taupin equations of dynamical diffraction. A uniform strain gradient has proven to be a valid model of strain deformations in the crystal.